Intensity and type of physical activity predicts depression in older adults. (3rd April 2021) - Mumba, Mercy Ngosa; Nacarrow, Alexandra F.; Cody, Shameka; Key, Betty A.; Wang, Hui; Robb, MacKenzie; Jurczyk, Abigail; Ford, Cassandra; Kelley, Mary Ann; Allen, Rebecca S.
Abstract: This study examined whether various levels of physical activity among older adults predicted levels of depression and whether there were racial differences in the levels and types of physical activities engaged in by adults aged 50 and older. Method: Data from the 2015-2016 National Health and Nutrition Examination Survey (NHANES) were analyzed for 2, 474 adults aged 50 years and older. Variables of focus were demographics, physical activity and depression, assessed using the Physical Activity Questionnaire and the Mental Health – Depression Screener. Results: There was a significant positive relationship between income and depression; individuals with higher income had lower levels of depression. Simple linear regression revealed income significantly predicted depression scores, b = –.20, F(1, 2296) = 96.35, p < .001, explaining 4% of the variance, R2 = .04. As age increased, all levels of physical activity declined, regardless of the category. Vigorous recreation-related activity and moderate recreation-related activity each made significant, unique contributions to depression scores. Conclusion: Findings from the current study suggest that physical activity interventions should be culturally appropriate and tailored to the needs and abilities of individual older adults to maximize benefits and minimize adverse events, particularly among community dwelling older adults.